Psychological aspects of law abiding behaviour of people - Valickas, Gintautas (Psichologija, 2001)
The article deals with different factors, which determine law abiding behaviour of people: 1) the detterent effect of punishment; 2) internalized values or internal standarts of behaviour; 3) behaviour of law enforcement officiers, which influence perceived justice or injustice. Some recommendations are presented how to improve the present situation.
Keywords: law abiding behaviour